Cluster-Electron Interaction for Poly-Anion Production. (August 2015) - Martinez, F; Bandelow, S; Marx, G; Schweikhard, L; Vass, A
Synopsis: By interaction with electrons in ion storage devices (ion-cyclotron-resonance and radio-frequency traps) negatively charged clusters of gold and aluminum have been produced up to the 6 th and 10 th charge state, respectively. The production of these poly-anions opens exciting new possibilities to measure their lifetimes, to monitor their relaxation schemes after laser radiation, as well as to probe their Coulomb barriers.